Mitigating the Risk of Organophosphate Pesticide Exposure through Community Empowerment of Farmers in Torongrejo Village, Batu City, East Java - Khambali; Rachmaniyah; Iva Rustanti Eri Wardoyo; Mujiyono; Heru Subaris Kasjono; Adella Putri Auliah Hapsari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
East Java is one of the provinces that serve as major producers of food commodities, particularly rice. In 2023, a total of 9.59 million tons of rice were harvested, with a productivity rate per hectare reaching 56.90 quintals. Lamongan was the leading regency in production in 2023, achieving 797.02 thousand tons. It is undeniable that this success is closely linked to the use of chemical substances (pesticides). Improper use of pesticides can trigger poisoning. A 2008 study reported an organophosphate pesticide poisoning rate of 50% among farmers in Sumberejo. Indiscriminate use of pesticides can lead to neurological health issues and hormonal effects. The presence of organophosphate pesticides in the body can be identified by elevated levels of cholinesterase in the blood. The approach method used in this community service involves conducting outreach to enhance farmers' understanding and knowledge about the dangers of pesticides, thereby fostering behavioral changes for the better. The aim of this activity is to increase farmers' knowledge and understanding of the signs or symptoms of organophosphate pesticide poisoning, as well as its management, handling actions for poisoning, and preventive measures using Personal Protective Equipment (PPE). This activity certainly involves all relevant government and health institutions that support the initiative.